Comparison of Antimicrobial Efficacy of IKI and NaOCl Irrigants in Infected Root Canals: An In Vivo Study - Abbaszadegan, Abbas; Khayat, Akbar; Motamedifar, Mohammad (Iranian Endodontic Journal, 2010)
INTRODUCTION: Effective debridement of the root canal system with chemical irrigants prior to obturation is the key to long-term success of endodontic therapy. The purpose of this study is to compare the antibacterial activity of 2.5% sodium hypochlorite (NaOCl) and 2% iodine potassium iodide (IKI) solutions as intracanal disinfectant in infected root canals during one-visit endodontic treatment procedure. MATERIALS AND METHODS: Thirty single-rooted teeth with necrotic pulps in 27 patients were selected according to specific inclusion/exclusion criteria and divided into two random groups. In group I, canals were irrigated with 2.5% NaOCl during instrumentation and in group II canals were initially irrigated with sterile saline during biomechanical preparation and then exposed to a 5-minute final irrigation with 2% IKI. Bacterial samples were taken before treatment (S1), and at the end of treatment (S2). Mann-Whitney U test was used for analysis. RESULTS: Bacteria were present in all initial samples. NaOCl was able to significantly reduce the number of colony forming units (CFU) from S1 to S2 in approximately 90% of canals. Only 15% reductions in CFUs occurred after irrigation/instrumentation in group II; this degree of disinfection was not statistically significant. CONCLUSION: According to this study, although root canal irrigation with 2.5% NaOCl could not eradicate all bacteria within the canals; it was significantly superior in comparison with 2% IKI use.